Corporate governance reforms, interlocking directorship networks and company value in Italy (1998-2007) - Carlo Drago; Francesco Millo; Roberto Ricciuti; Paolo Santella (Center for Economic Studies and ifo Institute (CESifo), 2011)
In this paper we contribute to the literature on the structure of interlocking directorship networks and to the literature on the relationship between corporate governance and performance. We use a unique dataset made of corporate governance variables related to the board size and interlocking directorships of the Italian companies listed in the stock exchange over 1998-2007. We find that the corporate governance reforms introduced over the period considered have shown some effectiveness by slightly dispersing the network of companies. Moreover, we find robust evidence that interlocking directorships has been negatively related with company performance.
Keywords: C14; C23; G34; L14; M21; 330; corporate governance; interlocking directorships; company performance; social network analysis; Corporate Governance; Reform; Unternehmensentwicklung; Eigentümerstruktur; Italien